76.1k views
2 votes
Simplify each exponential expression to the form x^n where n is positive.

Simplify each exponential expression to the form x^n where n is positive.-example-1
User Mony
by
5.5k points

1 Answer

3 votes

The expression is:


\sqrt{(x^(3)x^(8))/(x^(6))}

We will use following steps to simplify it:

Step 1:

Use product property of exponents:


x^(a)*x^(b)=x^(a+b)


x^(3)*x^(8)=x^(8+3)


x^(3)*x^(8)=x^(11)

That gives us the expression:


\sqrt{(x^(11))/(x^(6))}

Step 2:

Use division property of exponents:


(x^(a))/(x^(b))=x^(a-b)


(x^(11))/(x^(6))=x^(11-6)


(x^(11))/(x^(6))=x^(5)

This simplifies the expression:


\sqrt{x^(5)}

Step 3:

Writing the square root as power 1/2:


\sqrt{x^(5)}=x^{5*(1)/(2) }


\sqrt{x^(5)}=x^{(5)/(2) }

Answer:

The final simplified form in x^n form is :


x^{(5)/(2) }


User Yushizhao
by
5.6k points